2018
DOI: 10.5198/jtlu.2018.1235
|View full text |Cite
|
Sign up to set email alerts
|

Rail transit development in lagging regions: A development-oriented investment and financing approach

Abstract: Transportation infrastructure investment can play a significant role in promoting urban development. How can governments finance expensive rail transit investments and promote urban development in lagging regions? This paper reviews a case in Chongqing, China, a municipality that proactively invested in rail transit development through a mechanism of land value capture and guided rapid urbanization. We use path analysis to test the assumption that the rail transit system investment, which is directly linked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(56 reference statements)
2
2
0
Order By: Relevance
“…Specifically, an office unit located within a radius of 400 m from the nearest LRT station enjoys a premium of 0.637%, which significantly falls to about 0.232% within a radius of 401–800 m. Thus, the early hypothesis is rejected: nearby commercial properties increase less in value as the distance to the nearest LRT station decreases. These results support studies by Cervero ( 11 ), Cervero and Duncan ( 13 ), Ko and Cao ( 20 ), Xu et al ( 38 ), Mohammad et al ( 21 ), and Yu et al ( 68 ), which found that the highest price/rent premium is within a 400 m radius of the nearest urban rail transit station. These results also support a study by Nelson et al ( 37 ), who indicated that the impact of transit accessibility on office rent decreases significantly with increasing distance from the nearest LRT station.…”
Section: Conclusion Policy Implications and Future Worksupporting
confidence: 89%
See 1 more Smart Citation
“…Specifically, an office unit located within a radius of 400 m from the nearest LRT station enjoys a premium of 0.637%, which significantly falls to about 0.232% within a radius of 401–800 m. Thus, the early hypothesis is rejected: nearby commercial properties increase less in value as the distance to the nearest LRT station decreases. These results support studies by Cervero ( 11 ), Cervero and Duncan ( 13 ), Ko and Cao ( 20 ), Xu et al ( 38 ), Mohammad et al ( 21 ), and Yu et al ( 68 ), which found that the highest price/rent premium is within a 400 m radius of the nearest urban rail transit station. These results also support a study by Nelson et al ( 37 ), who indicated that the impact of transit accessibility on office rent decreases significantly with increasing distance from the nearest LRT station.…”
Section: Conclusion Policy Implications and Future Worksupporting
confidence: 89%
“…Source: Adapted from Xu et al (38).station decreases. These results support studies by Cervero(11), and Duncan(13),Ko and Cao (20), Xu et al(38), Mohammad et al(21), and Yu et al(68), which found that the highest price/rent premium is within a 400 m radius of the nearest urban rail transit station. These results also support a study byNelson et al…”
supporting
confidence: 89%
“…Governments have sought answers to the question of which brings more benefits in investing in transport between lagging and prosperous regions because transport investment among economically different areas could integrate the regional economy (He et al 2019), promote economic and urban development (Xiao et al, 2018), or harm the local industries in the lagging regions (Lall et al, 2004). Measuring Transport investment's effect on regional development requires various complicated methods, including conventional Benefit-Cost Analysis (BCA), Multi-Criteria Analysis (MCA), and Input-Output Modeling (IOM) (Rosik et al, 2022), which makes it complicated and difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Land value uplift related to rail transit can also provide a convincing rationale for engaging in land value capture, a mechanism by which the public sector seeks to recapture the value of benefits received by property owners or developers due to infrastructure improvements, and use these revenues to fund such improvements (Higgins & Kanaroglou, 2016;McIntosh, Newman, Trubka, & Kenworthy, 2017;Zhao & Levinson, 2012). Land value capture has become increasingly attractive as an alternative source of capital for financing rail transit projects, especially in circumstances with widespread fiscal restraints (Haider & Donaldson, 2016;McIntosh et al, 2017;Smith & Gihring, 2006;Xiao, Zhong, Zhou, & Zhou, 2018). However, empirical studies on the impact of rail system land value uplift interventions demonstrate mixed findings concerning the magnitude and direction of the results and a dramatic range of both positive and negative effects on residential property values (Debrezion et al, 2007;Diaz & Mclean, 1999;Higgins & Kanaroglou, 2016).…”
Section: Introductionmentioning
confidence: 99%